VERIFICATION OF A 3-D NUMERICAL MODEL FOR SPILLWAY AERATOR - Ozturk, Mualla; Aydin, M. Cihan (Mdpi, 2009)
In this study, the results of CFD obtained by using Fluent with respect to the air entrainment at spillway aerators are compared to the data of the physical model study and the results of some empirical equations presented by other investigators. The air entrainment rates obtained from the CFD analyses are in reasonable good agreement with the values calculated by the empirical equations. However, the CFD results are better than the physical model data including considerable scale effects. The numerical verification procedure in this study is based on the ASME editorial policy statement, which provides a framework for computational fluid dynamics uncertainty analysis. So, the validation of the CFD model was discussed in this scope.
Keywords: Air Entrainment; CFD; Fluent; Spillway Aerators